Towards Understanding Lignin Electrolysis: Electro-Oxidation of a β-O-4 Linkage Model on PtRu Electrodes. Issue 13 (28th September 2020) - Beliaeva, K.; Elsheref, M.; Walden, D.; Dappozze, F.; Nieto-Marquez, A.; Gil, S.; Guillard, C.; Vernoux, P.; Steinmann, S. N.; Caravaca, A.
Abstract : The reaction mechanism for lignin electrolysis has been rarely studied. In a previous work, we reported the electrolysis of lignin on a Polymer Electrolyte Membrane (PEM) alkaline electrolyzer with PtRu-based anodes. Even though the performance of this technology was proven in a low range of applied potentials (<1.2 V) and reaction temperatures (<90 °C), the activity of the system was strongly hindered, leading to low H2 production rates. The aim of this work is to study the main limitations of PtRu electrodes for lignin electro-oxidation. 2-Phenoxyethanol, 2-PE, has been chosen as a model molecule of the β -O-4 linkage, which represents ≈60% of the lignin bio-polymer. The performed electrochemical experiments, together with the HPLC analysis of the anodic products and the thermodynamic DFT computations, suggest that the electro-oxidation of the 2-PE organic molecule is very limited and leads to the production of the carboxylic acid as the final reaction product. In addition, the electro-catalytic system was severely poisoned, probably owing to the presence of some reaction by-products. All in all, this study allows advancing one step-forward towards understanding the reaction mechanism and the main limitations of the lignin electrolysis technology in the above described system.